The effectiveness of an early parenting intervention for mothers with infants with sleep and settling concerns: a prospective non-equivalent before-after design - Hauck, Yvonne; Hall, W.; Dhaliwal, Satvinder; Bennett, E.; Wells, G. (Wiley-Blackwell Publishing Ltd., 2012)
Aim: The study aim was to compare changes in maternal confidence, competence, depression, anxiety and settling behaviours and children’s sleep and settling behaviours for mothers and infants (4–6 months of age) attending a Day Stay intervention at an early parenting centre in Western Australia and a community group. Background: Infant difficulties in getting to sleep and frequent night waking are concerns for parents. Techniques are available to assist parents with infants exhibiting behavioural sleep problems; however, parents often lack confidence to consistently initiate sleep interventions. Design: The study incorporated a prospective non-equivalent before-after design. Method: The conceptual framework guiding this intervention emphasised the development of parental confidence and competence through connection with practitioners to promote change. Both groups provided baseline data (time 1) and four weeks postbaseline (time 2). Recruitment occurred between July 2007–July 2009. Results: The Ngala group (n = 93) and community group (n = 85) were not equivalent for infant age and maternal parity; there were more multiparous mothers in the community group, with infants on average one week older. The Ngala group, the majority of which were primiparous women, had significantly higher levels of competence and confidence four weeks following their Day Stay visit. There were no significant differences between groups at time 2 for time to settle the infant at night, infant night waking and maternal depression and anxiety scores. Conclusions: Although both groups demonstrated an improvement in depression and anxiety scores, with decreased sleep and settling concerns, the results indicate parental inconsistency in settling approaches. Given links between inconsistent infant settling approaches and infants’ difficulty with sleep self-initiation, further exploration is warranted. Relevance to clinical practice: The conceptual framework guiding the Ngala practitioners was effective in developing confidence and competence for the sample.